A Bi1/2K1/2TiO3-based ergodic relaxor ceramic for temperature-stable energy storage applications. (September 2021) - Wei, Yongxing; Zhang, Ning; Jin, Changqing; Shen, Jiahao; Xie, Jiahuan; Dai, Zhonghua; Hu, Lin; Zeng, Yiming; Jian, Zengyun
Graphical abstract: Highlights: A novel Bi1/2 K1/2 TiO3 -based ergodic relaxor ceramic was designed and prepared . The ceramic displayed large W rec (3.07 J/cm 3 ) and high η (>88%). The variation of  Wrec is less than ±2% between 30 and 150 °C. Abstract: Relaxor ferroelectrics are attractive for the high energy storage density. However, the polarization responses of most relaxor ferroelectrics are sensitive to temperature, thus leading to thermal-dependent energy storage properties. In this work, 0.5Bi1/2 K1/2 TiO3 –0.5SrTiO3 (0.5BKT–0.5ST) and 0.95(0.5Bi1/2 K1/2 TiO3 –0.5SrTiO3 )–0.05Bi(Zn1/2 Ti1/2 )O3 (BKT–ST–0.05BZT) ceramics were prepared using the solid-state reaction method. Both compositions showed an average cubic structure, with a relaxor-type dielectric anomaly. The rather low remanent polarization and delayed saturated polarization indicated the formation of the ergodic polar nano regions. Benefitting from the Bi(Zn1/2 Ti1/2 )O3 modification, the recoverable energy storage density ( W rec ) reached 3.07 J/cm 3 because of the enhanced polarization and increased bandgap. Meanwhile, BKT–ST–0.05BZT exhibited a high storage efficiency ( η  > 88%). When the specimen was heated from 30 °C to 150 °C, Wrec under the maximum electric field Em of 150 kV/cm varied from 1.58 to 1.63 J/cm 3 (＜ ±2%).